Assessment of Pedestrian Safety at Crosswalks of Unsignalized Intersection: A Case Study of Machhapokhari Intersection, Kathmandu - K.C., Hari Krishna; Shahi, Thusitha Chandani (Journal on Transportation System and Engineering, 2025)
The rapid urbanization of Kathmandu Valley, coupled with increasing vehicle and pedestrian traffic, has highlighted the critical need for pedestrian safety, particularly at intersections. Despite the growing number of vehicles and pedestrians, pedestrian safety remains a largely overlooked aspect of traffic management in Nepal. The Machhapokhari intersection, an unsignalized and uncontrolled junction, has been identified as dangerous for pedestrians, with high crash frequencies and pedestrian fatalities. This study focuses on assessing pedestrian safety using the Ordered Logit (OL) model at the Machhapokhari intersection. Pedestrian safety assessment was conducted using a structured questionnaire survey of 400 pedestrians crossing the crosswalks of the Machhapokhari intersection. The survey data were analyzed using an ordered logistic regression (OL) model to identify the qualitative factors influencing pedestrian safety perceptions. Key variables included pedestrian age, previous crash history, vehicle volume, road width, traffic control, and pedestrian behavior. Findings from the study indicate that younger pedestrians (age=15-24 years) and those controlled by traffic perceive higher safety levels. Factors such as traffic police control, pedestrian road markings, and less road width at crossings of pedestrians significantly improved the safety of pedestrians at the Machhapokhari intersection. Conversely, higher vehicle volume and speed were associated with lower safety perceptions. The research offers actionable insights for researchers and policymakers to study pedestrian safety at similar intersections across Kathmandu and other urban areas.